Interpersonal Trust Impact on Moderate Customer Satisfaction by Product Quality and Brand Image - Aloysia Pranata; Tantri Yanuar Rahmat Syah; Rina Anindita (Penerbit Kemala Indonesia, 2020)
Consumer satisfaction needs to be considered by company management due to affected by company's turnover. Consumer satisfaction appeased to buy a product because value factors that encourages this desire. This is evident from a several studies has been successful to show a significant influence of interpersonal trust on customer satisfaction which is also influenced by product quality and brand image. Previous Thus, in this study aims to analyze the effect of interpersonal trust on consumer satisfaction which is moderated by product quality and brand image. Here, we use ANOVA univariate analysis and using 120 respondents as in 2018. The result shows a interpersonal trust will increase customer satisfaction with a high interpersonal that a moderated by high product quality will increase by customer satisfaction, high interpersonal trust, and high brand image will increase customer satisfaction.